Map of Neuroethics - Dranseika, Vilius; Gefenas, Eugenijus; Noreika, Saulius (Problemos, 2009)
The article deals with the problems discussed in neuroethics a rapidly developing field of applied ethics. The term “neuroethics” is discussed in the article and is suggested to group neuroethical problems into four groups: (1) ethical problems connected with brain imaging technologies, (2) ethical problems connected with the technologies that allow to manipulate the activity and properties of the brain, (3) the influence of the neuroscientific worldview on our considerations on morality, and (4) general metaphilosophical considerations on neuroethics itself. The article concludes with a discussion of the relation between neuroethics and bioethics.